Indirect Evidence on Sex Reversal of Sinonovacula constricta (Bivalvia: Euheterodonta) and Gomphina veneriformis (Bivalvia: Veneridae) - Shin, Yun Kyung (Dev Reprod, 2014)
This study attempts to propose the possibility of the sex reversal in Sinonovacula constricta and Gomphina veneriformis by confirming the changes in the sex ratio with the shell length in the same population level. For analysis of sex ratio, 100 individuals of S. constricta (SL 26.5-95.0 mm) and 2385 individuals of G. veneriformis (SL 15.1-60.1 mm) were used. Sex was analyzed histologically. Both species displayed the tendency of increase in the female proportion with increase in shell length. In this study, changes in the sex ratio in accordance with the growth of S. constricta and G. veneriformis are determined to be indirect evidence that signifies their sex reversal.